EFFECT OF WELL WATER ON THE MECHANICAL PROPERTIES OF CONCRETE WITH USING TWO TYPES OF CEMENT - Wadie, Revan; Zidan, Roua; Ahmed, Tuqa (Journal of Applied Engineering Science, 2022)
The effect of using different water resources and cement types on concrete strengths at late ages is investigated. Two types of cement including Ordinary Portland Cement (OPC) and Sulfate Resisting Portland Cement (SRPC) were employed to prepare concrete mixes with potable and well water. Compressive, flexural, and tensile tests on were conducted at 28, 90 and 180 days. Results show that the maximum decreasing of concrete strength was about 42.9% at 180 days compared with the control mix when using well water with OPC. This was due to the chemical contents of well water that are more than the allowed limits. While the reduction in compressive strength was about 31.3% when using well water with SRPC due to sulfate resisting cement. Flexural strength reductions of 50.5% and 42.8% was seen when using OPC and SRPC respectively with well water at 180 days. Same effect was observed for tensile strengths which indicates that using well water has negative effect on concrete strengths at late ages. Modulus of elasticity was calculated using the ACI 318 equation. Higher reduction of 24.5% was seen when using OPC with well water than 17.2% when using SRPC with well water at 180 days compared to control mix.